Rasio neutrofil limfosit (RNL), mean platelet volume (MPV), serta red cell distribution width (RDW) sebagai prediktor tunggal sepsis neonatorum awitan dini (SNAD) di RSUD Wangaya Kota Denpasar, Bali - I Gusti Ayu Mahadewi; I Wayan Bikin Suryawan; I Gde Doddy Kurnia Indrawan (Intisari Sains Medis, 2022)
Background: Sepsis is still a serious world health threat, especially in developing countries, including Indonesia. Blood culture examination as the gold standard for diagnosis has several drawbacks, thus encouraging clinicians to find new markers with shorter examination times and affordable costs. This study examines the relationship between RNL, MPV and RDW with early-onset neonatal sepsis (EONS) at Wangaya Hospital, Denpasar City. Methods: This cross-sectional analytic observational study using the consecutive sampling method was carried out by collecting medical record data for neonates at risk for neonatal sepsis who were treated at the Wangaya Hospital, Denpasar City from January 2020 to September 2021. The cut off values for RNL, MPV and RDW were determined using a receiver-operating characteristic curve. (ROC). Chi-square analysis and multivariate logistic regression were performed to determine the significant relationship. Results: Of the 110 sample subjects, 57 subjects (47.5%) had a diagnosis of SNAD. The results of bivariate analysis, RNL with a cut off value of 2.23 (p<0.001), MPV with a cut off value of 9.95 fL (p<0.001), and RDW with a cut off value of 16.15% (p<0.001) were associated with EONS. The results of multivariate analysis showed that RNL (OR=3.32, p=0.012), MPV (OR=3.83, p=0.004), and RDW (OR=3.47, p=0.006) were the single predictors of EONS. Conclusion: neutrophil lymphocyte ratio (RNL), red cell distribution width (RDW), mean platelet volume (MPV) as independent predictor of early-onset neonatal sepsis (SNAD).   Latar Belakang: Sepsis saat ini masih merupakan ancaman kesehatan dunia yang serius, terutama di negara berkembang, termasuk Indonesia. Pemeriksaan kultur darah sebagai baku emas diagnosis memiliki beberapa kelemahan, sehingga mendorong klinisi untuk menemukan penanda baru dengan waktu pemeriksaan lebih singkat dan biaya terjangkau. Studi ini meneliti hubungan RNL, MPV serta RDW dengan sepsis neonatorum awitan dini (SNAD) di RSUD Wangaya, Kota Denpasar. Metode: Penelitian observasional analitik potong lintang ini menggunakan metode consecutive sampling dilakukan dengan mengumpulkan data rekam medis neonatus dengan resiko sepsis neonatorum yang dirawat di RSUD Wangaya Kota Denpasar dari Januari 2020 hingga September 2021. Nilai cut off RNL, MPV dan RDW ditentutkan menggunakan kurva receiver-operating characteristic (ROC). Analisis chi-square dan regresi logistik multivariat dilakukan untuk mengetahui hubungan yang bermakna. Hasil: Dari 110 subjek sampel, sebesar 57 subjek (47,5%) dengan diagnosis SNAD. Hasil analisis bivariat, RNL dengan nilai cut off 2.23 (p<0,001), MPV dengan nilai cut off 9,95 fL (p<0,001), serta RDW dengan nilai cut off 16,15% (p<0,001) berhubungan dengan SNAD. Hasil analisis multivariat, menunjukkan RNL (OR=3,32, p=0,012), MPV (OR=3,83, p=0,004), serta RDW (OR=3,47, p=0,006) merupakan prediktor tunggal kejadian SNAD. Simpulan: rasio neutrofil limfosit (RNL), red cell distribution width (RDW), mean platelet volume (MPV) sebagai prediktor tunggal sepsis neonatorum awitan dini (SNAD).